Assessment of control and monitoring system design security using the attack security tree analysis method - Mustafa Qahtan Alsudani; Israa Fayez Yousif; Ahmed Nooruldeen Alsafi; Hassan Falah Fakhruldeen (Institute of Advanced Engineering and Science, 2023)
Because of the efficiency of the system and the fact that it successfully completed the tasks that were given to it under specific conditions, we are compelled to look for a way to measure these requirements according to the conditions and guidelines that were established by the people who make use of the system. Conduct an investigation into the many techniques that are available for use in analysis in light of the following conditions: i) sufficient time to detect the mistake, ii) time to maintenance, iii) the total number of constituents involved in the analytical process, and iv) an explanation of the level of complexity provided to the user. In this article, we will provide a concise overview of a number of different approaches, along with our recommendations for the most effective ones based on the issues raised earlier.